2020
DOI: 10.3389/fpsyt.2020.00204
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophy of Oligodendrocytes and Adjacent Microglia in Prefrontal Gray Matter in Schizophrenia

Abstract: Background: Some evidence support the notion that microglia activation in acute state of schizophrenia might contribute to damage of oligodendrocytes and myelinated fibers. Previously we found dystrophic changes of oligodendrocytes in prefrontal white matter in schizophrenia subjects displaying predominantly positive symptoms as compared to controls. The aim of the study was to verify whether microglial activation might contribute to dystrophic changes of oligodendrocytes in prefrontal gray matter in this clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 94 publications
4
26
0
Order By: Relevance
“…Interestingly, these hub regions which process large amounts of information have high metabolic requirements, are characterized by the co-expression of genes regulating oxidative metabolism, and might be particularly sensitive to OxS [161]. WM abnormalities typically result from dystrophic alterations of oligodendrocytes at the ultrastructural, genetic, epigenetic and molecular levels [162][163][164]. Similarly to PV neurons, oligodendrocytes have a high metabolism to build and maintain the myelin sheets around the axons [165] and express elevated antioxidant enzymes (catalase and GPx) to prevent lipid peroxidation [166].…”
Section: Macrocircuit Dysfunction and Redox Dysregulation In Relation To Disrupted Myelination And White Matter Integrity Diffusion Propementioning
confidence: 99%
“…Interestingly, these hub regions which process large amounts of information have high metabolic requirements, are characterized by the co-expression of genes regulating oxidative metabolism, and might be particularly sensitive to OxS [161]. WM abnormalities typically result from dystrophic alterations of oligodendrocytes at the ultrastructural, genetic, epigenetic and molecular levels [162][163][164]. Similarly to PV neurons, oligodendrocytes have a high metabolism to build and maintain the myelin sheets around the axons [165] and express elevated antioxidant enzymes (catalase and GPx) to prevent lipid peroxidation [166].…”
Section: Macrocircuit Dysfunction and Redox Dysregulation In Relation To Disrupted Myelination And White Matter Integrity Diffusion Propementioning
confidence: 99%
“…These complex cells contribute to normal brain development and function by supporting the neuronal circuitry through synapse addition, elimination, maintenance, and plasticity (Hammond et al, 2018;Bohlen et al, 2019). Despite variability in the findings of several studies, there is evidence of microglial dysfunction in SCZ (Bayer et al, 1999;Hercher et al, 2014;Bloomfield et al, 2016;TrĂ©panier et al, 2016;De Picker et al, 2017;Sellgren et al, 2019;Uranova et al, 2020). A key element to understand the pathogenesis of SCZ is to discern how genetic and environmental risk factors intersect to alter microglial function given.…”
Section: Introductionmentioning
confidence: 99%
“…In cases of SCZ, Uranova et al, found that in the prefrontal white matter region, microglia activation contributed to dystrophic changes of oligodendrocytes ( 31 ). Furthermore, other studies show that in cases of SCZ, oligodendrocytes have lysed cytoplasm and form vacuoles in the surrounding tissue when they are found in close proximity to amoeboid microglia in cortical gray matter ( 54 ). These studies suggest that both cortical and WM activated microglia contribute to an inability to modulate normal brain function, which is exaggerated in cases of SCZ.…”
Section: Discussionmentioning
confidence: 99%